The study of the ozone influence on bovine serum albumin and cholinesterase by the optical spectroscopy methods - Belyh, I. A.; Dyubko, T. S.; Zinchenko, V. D. (Biophysical Bulletin, 2018)
From the experimental data submitted in clause follows, that action of ozone on biopolymers was accompanied by change of their spectral characteristics that testifies about conformations reorganizations and inactivation or stimulations of ferment activity. A degree of structural changes and ferment activity of biopolymers depend on concentration of ozone in environment of incubation. The handling by ozone small doses called a raise of cholinesterase activity, whereas the higher doses called ferment inactivation. The given property of ozone, probably, it is possible to apply as reactivate at reconservation a biological material after freezing.